Systematic literature review: Pengaruh media pembelajaran digital pada pembelajaran IPA terhadap literasi sains siswa SMP - Wahyuni, Sri; Yusmar, Firdha; Taniati, Rahmah; Bachtiar, Rayendra Wahyu; Noufal, Fatah An (Papanda Journal of Mathematics and Science Research, 2025)
Science literacy in science learning has a very important role to prepare qualified students who are able to compete in the international world. In reality, the level of science literacy among junior high school students are still relatively low. The solution that can be applied to improve student’s science literacy is to utilize digital learning media. The purpose of this study was to identify the effect of using digital learning media in science learning on the level of science literacy of junior high s chool students. This research method uses the SLR (Systematic Literature Review) method. This method is carried out with various activities, namely identifying, reviewing, evaluating, and interpreting all relevant research. The results of this study showed that all articles reviewed showed positive results in improving science literacy through the use of digital learning media. The conclusion that can be drawn is that digital learning media can be a solution to improve students' science literacy skills.